Transgenic rice Oryza glaberrima with higher CPD photolyase activity alleviates UVB-caused growth inhibition. Issue 1 (2nd January 2021) - Mmbando, Gideon Sadikiel; Teranishi, Mika; Hidema, Jun
ABSTRACT: The ultraviolet B (UVB) sensitivity of rice cultivated in Asia and Africa varies greatly, with African rice cultivars ( Oryza glaberrima Steud. and O. barthii A. Chev.) being more sensitive to UVB because of their low cyclobutane pyrimidine dimer (CPD) photolyase activity, which is a CPD repair enzyme, relative to Asian rice cultivars ( O. sativa L.). Hence, the production of UVB-resistant African rice with augmented CPD photolyase activity is of great importance, although difficulty in transforming the African rice cultivars to this end has been reported. Here, we successfully produced overexpressing transgenic African rice with higher CPD photolyase activity by modifying media conditions for callus induction and regeneration using the parental line (PL), UVB-sensitive African rice TOG12380 ( O. glaberrima ). The overexpressing transgenic African rice carried a single copy of the CPD photolyase enzyme, with a 4.4-fold higher level of CPD photolyase transcripts and 2.6-fold higher activity than its PL counterpart. When the plants were grown for 21 days in a growth chamber under visible radiation or with supplementary various UVB radiation, the overexpressing transgenic plants have a significantly increased UVB resistance index compared to PL plants. These results strongly suggest that CPD photolyase remains an essential factor for tolerating UVB radiation stress in African rice. As a result, African rice cultivars with overexpressed CPD photolyase may survive better in tropical areas more prone to UVB radiation stress, including Africa. Collectively, our results provide strong evidence that CPD photolyase is a useful biotechnological tool for reducing UVB-induced growth inhibition in African rice crops of O. glaberrima .